Research on extinguishing characteristics of nanocellulose-enhanced short-chain fluorocarbon foams for gasoline pool fires - Lu, Yawei; Liang, Shaolin; Cao, Xingyan; Wang, Zhirong; Lu, Haochen; Zhou, Yangqing (Applied thermal engineering, 2025)
•The average flame height gradually increases with the increase in fuel pan size.•Highest flame temperature increases with the increase of pool pan and oil layer.•Nanocellulose can improve the fire extinguishing and anti-burning performance.•Mastering the formula and mechanism is critical to suppress gasoline pool fires. The experiment was executed aiming at the combustion characteristics of fuel pool fire and the extinguishing performance of nanocellulose-enhanced short-chain fluorocarbon–hydrocarbon foam fire extinguishing agent. The influence law and mechanism of fuel pool flame characteristics were revealed through changing the fuel pan size, fuel layer thickness and ethanol ratio. Then, the fire extinguishing performance of nanocellulose-enhanced short-chain fluorocarbon–hydrocarbon foam extinguishing agent was investigated on this basis. The results showed that the maximum flame height (Hfmax) increased with the increase of the fuel pan size (from 20 cm to 60 cm) during the stable combustion stage. Both the Hfmax and the average flame height (Hf) increased with the increase of the fuel layer thickness (from 1.6 mm to 12.8 mm), but the increase rate was decreased continuously. With the ethanol content in gasoline increasing from 0 to 30 %, the initial flame height increased, but the flame combustion in the stable combustion stage decreased significantly. The maximum flame temperature increased gradually with the increase of fuel pan size and fuel layer thickness, but showed a trend of increasing and then decreasing with the increase of ethanol ratio. The mass loss rate increased gradually with the increase of fuel pan size and fuel layer thickness, but the increase rate slowed down with the increase of fuel layer thickness. Meanwhile, the maximum mass loss rate (MLRmax) and the average mass loss rate (MLRavg) during stable combustion increased slightly with the increase of ethanol ratio. It was also found that the addition of nanocellulose had a significant effect on the change of temperature field distribution during the fire extinguishing process, and with the increase of nanocellulose concentration, the flame temperature field showed a decreasing trend.